Desain Aplikasi Pengatur Anggaran Transaksi dan Neraca Keuangan Berbasis Mobile Menggunakan Metode User-Centered Design - Aditya, Edo Krishnanda; Gede Suhartana, I Ketut; Santiyasa, I Wayan; Santi Astawa, I Gede; Rahning Putri, Luh Arida Ayu; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Indonesians have very low financial literacy, which is the lowest level in ASEAN. According to ojk, only 38% have financial literacy. The purpose of this study is to solve this problem by utilizing the use of mobile phones in daily life. To solve this problem, the author uses user centered design as a prototyping and modeling technique to  create a design solution. Prototypes allow users to learn more about financial planning by creating budget plans and balance sheet plans. Users can also record  daily transactions so that they can see their financial status using  the application's audit menu. We hope that this application will improve Indonesian  financial literacy and help many people to lead a better financial life.